Editorial Note: JEiE Volume 10, Number 1 - Samantha Colón; Nathan Thompson; Dana Burde (Journal on Education in Emergencies)
In their Editorial Note accompanying JEiE Volume 10, Number 1, Samantha Colón, Nathan Thompson, and Dana Burde highlight the important contributions the authors featured in this issue make to education in emergencies scholarship and practice. In the research articles section, the contributing authors apply diverse, rigorous methodologies to practical questions in the education in emergencies field that relate to the opportunities and challenges of refining and scaling play-based learning; to the issues surrounding access to capacity-building initiatives for refugee teachers and for parents and caregivers in remote settings; and to the dynamics of intergroup contact, inclusion, and social hierarchy that are reflected in diverse learning spaces. The field notes section offers critical reflections on two adaptable, modular education in emergencies interventions: one is a place-based learning program centered on cultural heritage and young peoples' sense of belonging, and the other is a teacher wellbeing program based on building social-emotional competencies. Finally, the three book reviews featured in this issue highlight themes of belonging and connection to place, especially in the refugee experience, as well as stories of students and their communities being enabled to claim their agency, power, and a stake in a better future.